Analisis Wacana Makrostruktural Pemberitaan Ahok pada Pilkada DKI Jakarta 2017 - Vidya Mandarani; Nyoman Suwarta (Universitas Muhammadiyah Sidoarjo, 2017)
This study aims to find out the news macrostructural discourse analysis of Ahok in 2017 Jakarta’s election by using critical discourse analysis. This research applies the theory and method of Norman Fairclough critical discourse analysis in macrostructural dimension. This study is a qualitative research through the literature study on the media about Ahok in the Jakarta elections in 2017. From these results it can be concluded that the macrostructural analysis can be seen that the various media collected, it can be found that related to the upcoming elections in 2017 Jakarta’s election, namely Ahok during the campaign hampered charged with blasphemy. It can be used as a political motive for the purpose of winning the elections of Jakarta through the blasphemy case. One is the size of a political desire to prop Ahok through cases of blasphemy, because Ahok not successfully tackled through various other criminal cases.